TINJAUAN HUKUM TERHADAP PELAKSANAAN ASIMILASI DI RUMAH BERDASARKAN KEPUTUSAN MENTERI HUKUM DAN HAM REPUBLIK INDONESIA NOMOR M.HH-19.PK.01.04.04 TAHUN 2020 DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN COVID-19 BAGI NARAPIDANA - Moh Zakaria; Sri Sulistijaningsih (Faculty of Law - Tarumanagara University, 2020)
The Word Health Organization Regional Office for Europe issues Interim Guidance as a guide in dealing with the Covid-19 pandemic globally. Interim Guidance focuses on how to prevent and control Covid-19 in prisons or other places of detention. The guide explains that those who are in prison or other places of detention are more vulnerable to infections and covid-19 transmission. So that through the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number M.HH-19.PK.01.04.04 of 2020 released approximately up to 35 thousand inmates to prevent the transmission of Covid-19 in Correctional Institutions experiencing overcrowding. One such decision is regarding the application of assimilation at home. However, this decision contradicts the previous regulation regarding the implementation of assimilation that is regulated in the Minister of Law and Human Rights Regulation of the Republic of Indonesia Number 3 of 2018. To examine the problem in this article the author uses normative legal research methods, namely by reviewing the applicable laws and regulations and decisions that exist or apply to a particular legal problem / conflict. So that it can provide legal prescriptions and conclusions whether the implementation of assimilation in the house is legally legal. In a related regulation found the principle of mutatis mutandis in order to change the conditions of